Preface. Lecture Notes in Networks and Systems - Namasudra, Suyel; Chandra Trivedi, Munesh; González Crespo, Rubén; Lorenz, Pascal (Springer Science and Business Media Deutschland GmbH, 2024)
[Resumen no disponible]
Keywords: Computer Science: Signal Processing; Engineering: Control and Systems Engineering; Computer Science: Computer Networks and Communications; Scopus